Phytoseiid mites (Acari: Phytoseiidae) of the subfamily Amblyseiinae Muma from Peru, with descriptions of four new species - Guanilo, Alberto Daniel; de Moraes, Gilberto José; Knapp, Markus (Zootaxa, 2008)
This paper reports the mites of the subfamily Amblyseiinae (Phytoseiidae) known from Peru, based on an extensive survey conducted in different regions of the country as well as on published information. Forty-eight species are reported, four of which are new to science, namely Aristadromips escarsidentatus Guanilo & Moraes n. sp., Proprioseiopsis parabelizensis Guanilo & Moraes n. sp., Typhlodromips angustus Guanilo & Moraes n. sp. and Typhlodromips amazonensis Guanilo & Moraes n. sp. In addition to the description of the new species, measurements of all species collected and a taxonomic key to separate the species reported from Peru are provided.